Acute coronary syndrome or myocarditis? The role of multimodality imaging. (November 2014) - Alsaileek, Ahmed; Nasim, Mohammad; Aljizeeri, Ahmed; Alharthi, Mohsen; Al-Mallah, Mouaz H.
Abstract: The presentation of acute myocarditis varies. In some cases it mimics acute coronary syndrome. In this case we demonstrated the potential role of multi-modality cardiac imaging to quickly exclude coronary artery disease and confirm the diagnosis of myocarditis.